Pseudochroaptomus ecuadoriensis—a new genus and species of Philonthina and its systematic placement (Coleoptera: Staphylinidae: Staphylininae) - Chani-Posse, Mariana Raquel; Ramírez-Salamanca, José Manuel; Gualdrón-Díaz, Juliette Cristina (Zootaxa, 2024)
Pseudochroaptomus ecuadoriensis Chani-Posse et al., a new genus and species of the subtribe Philonthina (tribe Staphylinini) from the Tropical Andes of Ecuador, is described and illustrated. A dataset of 35 morphological characters scored for 23 taxa representing main clades of Philonthina, with focus on the Neotropical lineage and its subclades was prepared and analysed by maximum parsimony and Bayesian inference. Both analytical methods unambiguously placed Pseudochroaptomus as the sister-group of Chroaptomus Sharp.